(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Panjaitan RGP, Kristi Y, Irawan B, Salleh LM. 2024. Short Communication: Medicinal plants traditionally used to treat hypertension in Babane Village, Bengkayang, West Kalimantan, Indonesia. Biodiversitas 25: 3121-3129. One of the non-pharmacological treatments to treat hypertension is by herbal therapy using medicinal plants. This study aims to document medicinal plants to treat hypertension by the people of Babane Village, Bengkayang District, West Kalimantan, Indonesia. The method used in this research is the descriptive qualitative method. Data collection was carried out by semi-structured interviews and observations to informants selected using a purposive sampling method including traditional healers. This research documented 26 species of medicinal plants used traditionally as antihypertensives by the people in Babane Village consisting of Imperata cylindrica (L.) Raeusch., Ixora coccinea Comm. ex Lam., Eleutherine bulbosa (Mill.) Urb., Allium sativum L., Averrhoa carambola L., Pachyrhizus erosus (L.) Urb., Tinospora crispa (L.) Miers ex Hook.fil. & Thomson, Andrographis paniculata (Burm.fil.) Nees, Gymnanthemum amygdalinum (Delile) Sch.Bip. ex Walp., Physalis angulata L., Moringa oleifera Lam., Ricinus communis L., Mitragyna speciosa Korth., Phaleria macrocarpa (Scheff.) Boerl., Morinda citrifolia L., Phyllanthus niruri L., Annona muricata L., Eurycoma longifolia Jack, Hibiscus sabdariffa L., Piper crocatum Ruiz & Pav., Passiflora foetida L., Leonurus japonicus Houtt., Melastoma malabathricum L., Curcuma xanthorriza Roxb., Cucumis sativus L., Syzygium polyanthum (Wight) Walp. The leaves are the most commonly used part of the plant because of their antihypertensive properties while boiling is the most common processing technique.